2014
DOI: 10.4049/jimmunol.1303463
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid-Specific Disruption of Tyrosine Phosphatase Shp2 Promotes Alternative Activation of Macrophages and Predisposes Mice to Pulmonary Fibrosis

Abstract: The alternative activation of M2 macrophages in the lungs has been implicated as a causative agent in pulmonary fibrosis; however, the mechanisms underlying M2 polarization are poorly characterized. In this study, we investigated the role of the ubiquitously expressed Src homology domain–containing tyrosine phosphatase Shp2 in this process. Shp2 inactivation augmented IL-4–mediated M2 polarization in vitro, suggesting that Shp2 regulates macrophage skewing and prevents a bias toward the M2 phenotype. Condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
89
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(96 citation statements)
references
References 67 publications
6
89
1
Order By: Relevance
“…We hypothesize that SHP2 overexpression or inhibition promotes significant alterations in the phosphorylation states of several proteins involved in major signal transduction pathways. Because of the ubiquitous expression of SHP2 and its multitude of effects, it is possible that SHP2 inhibition may alter the general phosphorylation/dephosphorylation state of multiple signal transduction pathways in other cell types, not only fibroblasts, thus making the lung, as an organ, more susceptible to fibrosis, as has been previously described (19,20). This does not reduce the significant value of our observation that overexpression of catalytically active SHP2 has the potential to blunt fibrosis.…”
Section: Discussionmentioning
confidence: 43%
See 2 more Smart Citations
“…We hypothesize that SHP2 overexpression or inhibition promotes significant alterations in the phosphorylation states of several proteins involved in major signal transduction pathways. Because of the ubiquitous expression of SHP2 and its multitude of effects, it is possible that SHP2 inhibition may alter the general phosphorylation/dephosphorylation state of multiple signal transduction pathways in other cell types, not only fibroblasts, thus making the lung, as an organ, more susceptible to fibrosis, as has been previously described (19,20). This does not reduce the significant value of our observation that overexpression of catalytically active SHP2 has the potential to blunt fibrosis.…”
Section: Discussionmentioning
confidence: 43%
“…Global SHP2 deficiency is embryonically lethal in mice, due to major developmental defects (33,36). Support for a potential role for SHP2 in lung fibrosis has emerged from observations that targeted genetic ablations of SHP2 in AECs (19) or macrophages (20) are profibrotic. However, these studies did not assess the expression of SHP2 in human pulmonary fibrosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…M2 macrophage activation has been implicated in the development of pulmonary fibrosis (61)(62)(63) (Figures 2E, F). This finding indicates that inflammation was equivalent in BLM-challenged wild-type and α7 nAChR knockout mice, which could explain why deficiency of α7 nAChR did not affect BAL protein levels, an index of lung epithelial and endothelial permeability ( Figure 1).…”
Section: Ly6cmentioning
confidence: 99%
“…Compared with protein tyrosine kinases, much less is known about the role of PTPs in fibrogenesis. Genetic deletion of SHP2 in alveolar epithelial cells results in spontaneous pulmonary fibrosis in mice, possibly related to dysregulated surfactant homeostasis (10); similarly, genetic deletion of SHP2 in macrophages enhanced bleomycin-induced pulmonary fibrosis in mice, possibly by M2-skewing of the pulmonary inflammatory response (11). We have reported that mice genetically deficient in PTPa are protected from experimental pulmonary fibrosis (12).…”
Section: Taking It Off: New Insights Into the Role Of Tyrosine Phosphmentioning
confidence: 99%